1998
DOI: 10.2527/1998.7641019x
|View full text |Cite
|
Sign up to set email alerts
|

Beef color update: the role for vitamin E.

Abstract: Dietary supplementation of livestock with vitamin E results in improved quality of meat subsequently obtained from these animals. The effect is especially noteworthy in cattle, in which the primary effects are delayed discoloration and lipid oxidation. A threshold level of alpha-tocopherol in muscle ensures a detectable effect; dietary strategies for attaining this threshold must consider tocopherol status of cattle arriving at the feedyard and duration and level of supplementation. The alpha-tocopherol concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 43 publications
6
70
0
8
Order By: Relevance
“…Besides, the results suggest that the degradation of beef sensory quality was related to lipid and pigment oxidation, as reported by Liu et al (1995) and Faustman et al (1998). In this study, meat from Asturiana de los Valles and Morucha showed TBA .5 ppm after 10 days of storage ).…”
Section: Multiple Regression Analysissupporting
confidence: 76%
“…Besides, the results suggest that the degradation of beef sensory quality was related to lipid and pigment oxidation, as reported by Liu et al (1995) and Faustman et al (1998). In this study, meat from Asturiana de los Valles and Morucha showed TBA .5 ppm after 10 days of storage ).…”
Section: Multiple Regression Analysissupporting
confidence: 76%
“…It is a powerful inhibitor of iron-driven hydroxyl radical formation because of its ability to form a unique iron chalete that becomes catalytically inactive (Graf and Eaton, 1990). Vitamin E is a membrane-associated antioxidant and dietary vitamin E supplementation highly suppressed lipid oxidation (Morrissey et al, 1998, O'Neill et al, 1999, Ruiz et al, 1999 and delayed metmyoglobin formation (Jensen et al, 1998, Faustman et al, 1998. It stabilises PUFA and cholesterol in muscle against oxidative deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, vit. E is able to protect meat from lipid oxidation, with its color-stabilizing effect indirectly by delaying oxymyoglobin oxidation through the inhibition of lipid oxidation [29].…”
Section: Effect Of Dietary Vitamin E Supplementationmentioning
confidence: 99%
“…Consequently, this antioxidant mixture was able to stabilize beef color from PUFA rich beef by limiting lipid oxidation, as already proposed for vit. E in standard meats [29]. We calculated the correlation between MDA content from PUFA rich meat from ST muscle stored under modified atmosphere packaging, which represent the most deleterious conditions regarding lipid oxidation [7] (Figure 1).…”
Section: Effect Of Dietary Vitamin E Supplementationmentioning
confidence: 99%
See 1 more Smart Citation